Implementasi Tawakal sebagai Strategi Coping Stress pada Mahasiswa Rantau: Studi Kasus Mahasiswa PBSB Angkatan 2017 - Syisillia Syisillia (Gunung Djati Conference Series, 2023)
Overseas students are different from students in general who study in their own city. Different in terms of stress received. The stress experienced by overseas students is more than students who do not migrate. And the consequences not only have an impact on the psychological but also physical. And it's quite heavy. The reason for this problem makes researchers want to find solutions to these problems by using the method of implementing tawakal as a stress coping strategy. Tawakal itself according to the Sufis is an inner charity and work is a sunnatullah practice, this must go hand in hand in order to create a peace of heart for peace of mind and soul. The results of this study indicate that, by putting their trust in Allah, the 2017 PBSB overseas students become calmer, avoid anxiety and overthinking and have a healthy mentality. It is hoped that this paper will be able to provide benefits for students who will migrate and readers to be more aware of the stress that attacks when they migrate.